The Existence of Huyula Local Wisdom Values in the Character Education of Students at State Vocational High School 1 Limboto - Adjie, Zulfikar; Yunus, Rasid; Wantu, Asmun W.; Mawahda, Nurul (Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the existence of the value of Huyula in the character education of students at SMK Negeri 1 Limboto and to examine the factors influencing its actualization within school life. Huyula is a local wisdom value of the Gorontalo community, referring to cooperation, mutual assistance, and social solidarity grounded in a spirit of togetherness and collective responsibility in communal life. The study employs a qualitative approach with a case study design, utilizing interviews, observations, and student perception questionnaires as data collection techniques. The findings indicate that the value of Huyula continues to exist in students’ social practices, manifested through collective work and mutual support; however, it has not yet been internalized as a reflective character consciousness. The actualization of this value is constrained by structural, pedagogical, and cultural factors. This study underscores the importance of systematically and reflectively strengthening character education based on local wisdom, so that the value of Huyula can transform into a sustainable and deeply rooted character disposition.